The association between Tai Chi exercise and safe driving performance among older adults: An observational study - Miller, Sally (J Sport Health Sci, 2018)
BACKGROUND: Age-related cognitive and physical decline can impair safe driving performance. Tai Chi exercise benefits cognitive and physical function and may influence safe driving performance in older adults. The primary aim of this observational study was to compare cognitive processes and physical function related to safe driving performance among older adult Tai Chi practitioners to normative reference values. Secondary aims were to examine relationships between Tai Chi exercise habits, cognitive processes, and physical function related to safe driving performance and to explore potential predictors of safe driving performance. METHODS: The DrivingHealth Inventory, the Driving Scenes Test, other driving-related cognitive and physical measures, and self-reported measures including the Mindful Attention Awareness Scale (MAAS) and the Vitality Plus Scale (VPS) were collected from current Tai Chi practitioners (n = 58; age 72.9 ± 5.9 years, mean ± SD) with median >3 years Tai Chi practice. RESULTS: Compared to normative reference values, participants performed better on numerous cognitive measures including the Driving Scenes Test (p < 0.001, d = 1.63), maze navigation (p = 0.017, d = 0.27), the Useful Field of View Test (p < 0.001, r = 0.15), and on physical measures including the Rapid Walk Test (p < 0.001, r = 0.20), and the Right Foot Tapping Test, (p < 0.001, r = 0.35). Participants scored higher than normative reference values on MAAS and VPS (p < 0.001, d = 0.75; p = 0.002, d = 0.38, respectively). Statistically significant correlations were found between several study measures. The digit span backward test was the strongest predictor of safe driving performance (β = 0.34, p = 0.009). CONCLUSION: Tai Chi exercise has the potential to impact cognitive processes and physical function related to safe driving performance. Further study using randomized controlled trials, structured Tai Chi exercise doses, and driving simulator or on-road driving performance as outcome measures are warranted.